The promised land [videorecording (DVD)] - Arcel, Nikolaj; Jensen, Anders Thomas, 1972-; Mikkelsen, Mads, 1965-; Collin, Amanda; Bennebjerg, Simon; Hagberg, Melina; Thorp, Kristine Kujath, 1992-; Lindh, Gustav, 1995-; Jessen, Ida, 1964- (Magnolia Home Entertainment, 2024)
Captain Ludvig Kahlen sets out to tame an uninhabitable land and build a colony in the name of the King. While braving the elements, he is joined by some indentured serfs who have fled their tyrannical magistrate, which makes them all targets of a deadly conflict.